Pengaruh Konsentrasi Air Rendaman Sabut Kelapa dan Dosis Pupuk NPK Terhadap Pertumbuhan dan Hasil Tanaman Melon Varietas Action 434 - Romiyadi Romiyadi; Endang Sufiadi (Paspalum: Jurnal Ilmiah Pertanian, 2015)
The experiment was conducted at Faculty of Agriculture UNWIM Tanjungsari - Sumedang, at the altitude of 850 m above sea level (asl) with ground Andisol orders from February to April 2008. The purpose of an experiment to study the effect of the interaction between the concentration of coco water immersion ata dose NPK fertilizer on the growth and yield of melon varieties Action 434. The experimental design used was a randomized block design factorial design consisting of two factors and repeated twice. The first factor is the concentration of water immersion coco (k), which consists of five levels, namely: k0 = 0%, 25% = k1, k2 = 50%, k3 = 75%, and k4 = 100%. The second factor is the dose of NPK fertilizer (d),which consists of four levels, namely: d0 = 0 g plant-1, d1 = 10 g plant-1, d2 = 20 g plant, and d3 = 30 g plant-1. The results showed that there is an interaction effect between the concentration of coco water immersion at a dose of NPK fertilizer to the plants age 20 DAT (days after transplanting) and 30 DAT, as well as the number of leaves at the age of 30 DAT. Coco water immersion at a concentration of 25% gives a better effect on the variable length of the plant, number of leaves, fruit weight per plant, and the quality of the fruit skin. Coco water immersion at a concentration of 50% gives better effect on thevariable sweetness of the fruit flesh. Without dosing NPK fertilizer already gives a better effect on the variable length of the plant, number of leaves, fruit weight per plant, diameter of fruit per plant, and the thickness of the flesh of the fruit. NPK fertilizer dose of 10 g plant-1 give better effect to the variable length of the plant, number of leaves, fruit weight per plant, diameter of fruit per plant, the thickness of the flesh of the fruit, the sweetness of the fruit, and the quality of the fruit skin.